2020
DOI: 10.1080/23748834.2020.1848327
|View full text |Cite
|
Sign up to set email alerts
|

Exploring urban health inequities: the example of non-communicable disease prevention in Indore, India

Abstract: The dynamics of urban settings can increase health disparities. This paper explores techniques for examining urban health inequities of non-communicable disease risk, using data from the city of Indore, Madhya Pradesh, India as an example. We analyzed non-communicable disease indicators by gender, wealth, education, slum status, housing type, and location, using a 2018 city-level dataset collected in Indore with a final sample size of 3,070. Four techniques for equity analysis were used including bivariate rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…This paper uses a recent NCD survey from Indore City, India to explore whether there is any disparity in these community-level elements of the built environment and access to goods and services that in uence NCD risk. This analysis complements two previous papers using this dataset, which explored individuallevel risk factors that contribute to NCD risk, including gender, wealth, education, and housing status (Bachani et al, 2021;Pomeroy-Stevens et al, 2020).…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…This paper uses a recent NCD survey from Indore City, India to explore whether there is any disparity in these community-level elements of the built environment and access to goods and services that in uence NCD risk. This analysis complements two previous papers using this dataset, which explored individuallevel risk factors that contribute to NCD risk, including gender, wealth, education, and housing status (Bachani et al, 2021;Pomeroy-Stevens et al, 2020).…”
Section: Introductionmentioning
confidence: 74%
“…Prevalence of harmful use of alcohol (heavy episodic drinking) in Indore is low. The authors found a citywide prevalence rate of 2%, while in slums it was 3% (Pomeroy-Stevens et al, 2020). Overall tobacco use prevalence was 21%, and 31% in slums.…”
Section: Tobacco and Alcohol Environmentmentioning
confidence: 90%
See 3 more Smart Citations